World Health Organization guidelines, the COVID-19 pandemic, and transnational law - Márcio Cruz, Paulo (2020)
The reflections within this paper discuss the importance of transnational law, following the onset of the COVID-19 pandemic. In addition, considerations are made about the transnational law produced by the World Health Organisation (“WHO”) against COVID-19. Also, an analysis will be made of the central categories and their relationship with the prefix “trans” and transnational law. Subsequently, the WHO as an entity is discussed along with its emergence and performance in the elaboration of a transnational legal framework, which is to be considered when internalising its guidelines by each Member State. In the context of final considerations, it is emphasised that, in addition to the importance that should be attributed to transnational law, the work of WHO, as a transnational actor, practices materialised acts such as transnational law, both in terms of guidance and in connection with public health matters. The methodology used was based on the inductive method, using the bibliographic research.